Safety attitudes and beliefs of junior Australian football players. Issue 2 (1st June 2002) - Finch, C; Donohue, S; Garnham, A
Abstract : Objectives: To describe the safety attitudes and beliefs of junior (aged 16–18 years) Australian football players. Setting: Six Victorian Football League Under 18 (VFL U18) clubs in Victoria, Australia. Methods: Cross sectional survey. Altogether 103 players completed a self report questionnaire about their safety beliefs and perceptions of support when injured, across three contexts in which they played: VFL U18 club, local club, and school. Results: Although only 6% believed it was safe to play with injuries, 58% were willing to risk doing so. This increased to almost 80% when players perceived that their chances of being selected to play for a senior elite team would be adversely affected if they did not play. There were significant differences in the perceived level of support for injured players and in the ranking of safety as a high priority across the three settings. In general, the VFL U18 clubs were perceived as providing good support for injured players and giving a high priority to safety issues, but local clubs and particularly schools were perceived to address these issues less well. Conclusions: Junior Australian football players have certain beliefs and perceptions in relation to injury risk that have the potential to increase injuries. These negative beliefs need to be addressed in any comprehensive injury prevention strategy aimed at these players.